ANALISIS KESEDIAAN MEMBAYAR JASA LINGKUNGAN DALAM PENGELOLAAN SUMBERDAYA AIR MINUM TERPADU DI INDONESIA (STUDI KASUS DAS CISADANE HULU) - Sutopo, Muhammad Fauzi; Sanim, Bunasor; Saukat, Yusman; Mawardi, Muhammad Ikhwanuddin (Jurnal Teknologi Lingkungan, 2011)
Ecocentrism paradigm in development are intended to ensure the sustainability of water resources in the future for future generations. The research methodology was conducted with the model approach to drinking water users willingness to pay for environmental services (YWTP). The results in Analysis Willingness to Pay in Drinking Water Management in the Upstream Watershed Cisadane illustrates that the existence of a positive response from drinking water users (entrepreneurs) to be willingness to pay for environmental services (YWTP) as payment and reward for environmental services to the public because it is influenced by the presence and the beneficiaries are significantly linearly with level of education (sig. 0.041) and Variable in YWTP education significant at 95% confidence level. Policy implications of this research that the user (downstream) is willingness to pay (WTP) for environmental services with averaging Rp1 538.65 per m3 as payment or reward for environmental services to society (upstream), so the Government (Local) PES has a potential revenue to fund conservation of Rp106.94 billion per years, but in current conditions the government only earns Rp20.57 billionper year, so that only reached 19.24%.